Community Perceptions and Environmental Conditions Around the Tegalgondo and Kepuharjo Temporary Trash Shelter Sites, Karangploso Sub-District - Nunuk Setia Indriyana; Ratna Djuniwati L; Saimul Laili (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2021)
Community behavior in disposing of waste plays an important role in improving public health. Community participation is needed to reduce the amount of waste, especially the role of housewives. Efforts to reduce the amount of household waste require support, one of which is the public perception of household waste processing. So far, people do not have the habit of sorting and selecting waste so that the amount of waste disposed of at TPS continues to increase. This increase can affect the environmental conditions around the TPS if there is an accumulation of waste in the long term. This study aims to analyze public perceptions of TPS Tegalgondo and TPS Kepuharjo and to analyze the environmental conditions around TPS Tegalgondo and TPS Kepuharjo in Karangploso District. The method used in this research is descriptive quantitative and direct field surveys. Based on the results of research conducted. The results of public perceptions of TPS Kepuharjo got very high perceptual scores about household waste management and low perceptions about TPS. The results of the analysis of environmental conditions at TPS Tegalgondo for the total risk value is 170 which is included in the medium category which means it requires high level management attention. The results of the analysis